Answer: The solutions of the given equation in increasing order are
![x=-(1)/(2),~0,~(3)/(2).](https://img.qammunity.org/2019/formulas/mathematics/middle-school/6n7s2shb07bk8coajycn6iveza3lxxk66m.png)
Step-by-step explanation: The given equation is
![4x^3-5x=|4x|~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/m7dxhs1d9uifufpyb1cm43f5gacdaaeoqc.png)
We are to solve the above equation and to list the solutions in increasing order.
We know that
![|x|=a~~~~~~\Rightarrow a=x~~\textup{or}~~a=-x.](https://img.qammunity.org/2019/formulas/mathematics/middle-school/7u4yshoqma4juouc9bze1eqwcg6u2ll52v.png)
So, from equation (i), we get
![4x^3-5x=4x~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(iii)\\\\\textup{or}\\\\4x^3-5x=-4x~~~~~~~~~~~~~~~~~~~~~~~~~~~~(iv)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/qwdelp6mkzalf4c49hffw0ap5x4ym2x2r6.png)
Solving equation (iii), we get
![4x^3-5x=4x\\\\\Rightarrow 4x^3-9x=0\\\\\Rightarrow x(4x^2-9)=0\\\\\Rightarrow x=0,~~4x^2-9=0~~\Rightarrow x^2=(9)/(4)~~\Rightarrow x=\pm(3)/(2).](https://img.qammunity.org/2019/formulas/mathematics/middle-school/vehcnbq65xrdoydumwmcjpqm889bexdqmz.png)
So, solutions of equation (i) are
![x=0,~(3)/(2),~-(3)/(2).](https://img.qammunity.org/2019/formulas/mathematics/middle-school/kkq0ha7rl1tjretr4cf8qxwj3vino284pc.png)
And, solving equation (iv), we get
![4x^3-5x=-4x\\\\\Rightarrow 4x^3-x=0\\\\\Rightarrow x(4x^2-1)=0\\\\\Rightarrow x=0,~~~4x^2-1=0~~\Rightarrow x^2=(1)/(4)~~~\Rightarrow x=\pm(1)/(2).](https://img.qammunity.org/2019/formulas/mathematics/middle-school/1e4n32wkt1smjb0obxeud3vdtzq2hxc17t.png)
So, solutions of equation (ii) are
![x=0,~(1)/(2),~-(1)/(2).](https://img.qammunity.org/2019/formulas/mathematics/middle-school/8g7gp096ldh8oxnpb0npi6e7d2m1lyumyv.png)
We can see that
does not satisfy equation (i).
For
we have
![L.H.S.=4*(1)/(8)-5*(1)/(2)=-2,\\\\R.H.S.=|4*(1)/(2)|=2\\eq L.H.S.](https://img.qammunity.org/2019/formulas/mathematics/middle-school/lu7aa7cad9k7ulp7ir0dfeu9j32fuljyut.png)
Similarly, for
we have
![L.H.S.=4* -(27)/(8)+5*(3)/(2)=-6,\\\\R.H.S.=|4* -(3)/(2)|=6\\eq L.H.S.](https://img.qammunity.org/2019/formulas/mathematics/middle-school/sw5ej2f9vtthsie5au3fi4lqd8bl6hoyvh.png)
Thus, the solutions of the given equation in increasing order are
![x=-(1)/(2),~0,~(3)/(2).](https://img.qammunity.org/2019/formulas/mathematics/middle-school/6n7s2shb07bk8coajycn6iveza3lxxk66m.png)